Evaluation of Ultrasonography in Various Causes of Pelvic Pain in first Trimester of Pregnancy - AB Hussain, SMY Farooq, S. Qayyum, M. Yousaf, SB Hussain, MZU Abidin, P Jalal, L Arif, A. Ramzan, H. Noor, M. Suhail, SM Ammar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acute pelvic discomfort in pregnant and postpartum people can be difficult to diagnose and treat. Ultrasound is still the most common imaging modality used to evaluate pregnant and postpartum women. Aim: To see how useful ultrasonography is in evaluating several causes of pain in pelvic during early pregnancy. Methodology: A descriptive study was conducted at University of Lahore Teaching Hospital. Data of 344 participants were designated done suitable sample method. SPSS version 25 was used for data analysis. Results: In this table, 344 patients with pelvic pain are reported; 108 (31.4%) patients had bleeding, 58(16.9%) had fibroids out of 344 patients, 60 (17.4%) had cyst and 19 (5.5%) patients had ectopic pregnancy, 236 patients were not count for bleeding status in which 223 (94.5%) patients had no ectopic pregnancy & 13 (5.5%) patients had ectopic pregnancy. 108 patients were count for bleeding status, in which 6 (5.6%) patients had ectopic pregnancy & 102 (94.4%) patients had not ectopic pregnancy, 236 patients were not count for bleeding status in which 235 (99.6%) patients had no fibroids & 1 (0.4%) patients had fibroids. Conclusion: Fibroids and cysts were the most common findings in female with pain in pelvic in early pregnancy. Key words:Pain inLower abdominal, early pregnancy, first trimester, fibroid, Gestational sac, crown lump length.